Factors affecting theft and mutilation of library materials in the U.P. Diliman Main Library - Operario, Iris Marigold P.; Cruz, Ma. Divina P. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1998)
The purpose of this study is to determine the factors affecting theft and mutilation of library materials and the possible preventive measures in lessening these library crimes as perceived by the library users and the librarians in the UP Diliman Main Library.
The study utilized the descriptive-normative survey method and the instrument used for data gathering was a questionnaire. The subjects of the study were the UPDML users and the section heads of the Arts and Letters, Filipiniana - Books, Filipiniana - Serials, General Reference and Social Science sections.
The number of library user respondents was determined through the use of the Parten's formula for the size of respondents. The size of the sample yielded 281 respondents but 274 questionnaires were returned.
The top 5 factors considered by the library user respondents which greatly affect theft and mutilation were (1) cannot be taken out from the library and the material is badly needed by the user (library/situational factor); (2) too lazy to copy the material or have it photocopied (psychological/behavioral factor);(3) many difficult assignments which require the frequent use of the library (academic factor); (4) cannot afford to have the material photocopied (economic factor); and (5) inadequate number of copies of books and other materials (library/situational factor).The library users recommended the following solutions in minimizing theft and mutilation of library materials: (1) buy or have additional copies of books; (2) install more photocopying machines; (3) lower the price of photocopying; (4) longer library hours; and (5) hiring of more efficient and friendlier library staff.
Similar with the library clients' perceptions, all 5 section heads in the UPDML believed that (1) many difficult assignments which require the frequent use of the library; (2) cannot be taken out from the library and (3) do not consider the needs of others lead users to acts of theft and mutilation. All 5 of them believed that there is a need for a stricter and more meticulous checking of bags and folders if outgoing users to lessen the theft and mutilation in UPDML.
In view of the findings from the study, the following are recommended: (1) the UPDML should have multiple copies of in-demand books especially the ones in the reserve section; (2) there should be 2 black and white and 1 color photocopying machines in each section of the UPDML at reasonable service rates and for use of the library clients at any given time; (3) more library staff and student assistants should be hired for longer library hours to be possible; (4)the Filipiniana - Books and the charging desks in all sections should be opened on lunch breaks; (5) the UPDML should have information campaigns which educate the users on the replacement costs of stolen and mutilated books and periodicals; and (6) the charging system for books and other materials be made as simple and fast as possible by having more attending librarians and student assistants at the charging desk.
Computer print out.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Book thefts -- Philippines -- Quezon City; University of the Philippines Diliman Main Library